A STEAM approach supported by the meaningful learning theory to teach the solar system in lower secondary education (9th grade) - Batista, Michel Corci; Cintra Reinisz, Ivana Kelly; Vieira, Taisy Fernandes; Gomes, Ederson Carlos; Santos, Oscar Rodrigues dos; Silva Filho, Olavo Leopoldino da; Ferreira, Marcello (Frontiers in Education, 2025)
This article presents an innovative interdisciplinary approach to teaching the solar system in lower secondary education (9th grade), grounded in David Ausubel’s Meaningful Learning Theory and the STEAM (Science, Technology, Engineering, Arts, and Mathematics) methodology. Traditional astronomy teaching often fails to connect with students’ prior knowledge, resulting in superficial and fragmented learning. Addressing this issue is crucial for fostering deeper cognitive engagement and preparing students for complex, interdisciplinary challenges. However, there is a notable gap in the literature regarding integrating Ausubel’s theory with the STEAM approach, particularly in astronomy education at the lower secondary level. The study, conducted with 9th-grade students, employed active learning strategies such as planetarium visits, hands-on model construction, mind mapping, and collaborative projects to foster a holistic understanding of astronomical concepts. The proposal aimed to bridge prior knowledge with new content by integrating these methods, promoting critical thinking and creativity. Results demonstrated significant improvements in students’ ability to articulate and apply astronomical knowledge, highlighting the effectiveness of combining theoretical frameworks with experiential and interdisciplinary activities. The study underscores the potential of such approaches to address challenges in astronomy education, preparing students for contemporary cognitive demands while cultivating a deeper appreciation for the cosmos.